PRAKTIK LELANG DI INSTAGRAM YANG MENYESATKAN DITINJAU DARI UNDANG-UNDANG PERLINDUNGAN KONSUMEN - Ajeng Yudhangkara Witansaputri (2023)
The development of the internet world and technological advances are currently increasing rapidly, requiring that all types of transactions do not have to be done face to face. As one example of a buying and selling transaction that is currently developing is through an auction of goods. There are many online auction accounts that abuse the auction system in their buying and selling practices, one of which is an account named @auctioncool. Arrangements regarding the auction of goods are regulated in Article 11 of Law No. 8 of 1999 concerning Consumer Protection. With that in mind, this research seeks an answer from how business actors violate auctions that mislead consumers. As well as forms of legal responsibility that must be carried out by business actors due to auction practices that mislead consumers, using normative juridical research methods. Because there are still many auction accounts on Instagram social media which often mislead consumers and the business actors are not aware of the form of responsibility that must be implemented in running their business. The author also concludes that the auction on Instagram only uses the auction method and is not an official auction site and the account owner has violated consumer rights as stipulated in Article 11 of Law no. 8 of 1999 concerning Consumer Protection. The form of dispute resolution carried out to resolve disputes over consumer protection violations includes Article 11 according to the system of Law no. 8 of 1999 concerning Consumer Protection, consists of two types, namely: it can be through the general court, and it can also be through channels outside the court.